2009
DOI: 10.1111/j.1365-2524.2009.00857.x
|View full text |Cite
|
Sign up to set email alerts
|

Offender health and social care: a review of the evidence on inter-agency collaboration

Abstract: The involvement of health and social care agencies in crime reduction partnerships remains key to government strategy despite a growing awareness of the equivocal outcomes of inter-agency working in other settings. This paper reports findings from a literature review designed to assess the extent to which existing crime reduction partnerships have been able to overcome the barriers to joint working. The review focuses in particular on Drug (and Alcohol) Action Teams (D(A)ATs), Crime and Disorder Reduction Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 16 publications
(35 reference statements)
0
19
0
3
Order By: Relevance
“…A comprehensive review of the evidence on interagency collaborations in offender health and social care, including MAPPA, introduced by successive Labour administrations since 1997, revealed that although this subject area is awash with literature in the form of government policy, opinion and national evaluations, there is little independent research and systematic review. 4 The current evidence available confirms the presence of continued structural, procedural and cultural barriers that impede effective partnership working in interagency collaborations aimed at crime reduction. Key difficulties include conflicting targets imposed by individual agencies, and divergent ethical and professional values of the different agencies involved across the care control divide.…”
Section: Challengesmentioning
confidence: 73%
“…A comprehensive review of the evidence on interagency collaborations in offender health and social care, including MAPPA, introduced by successive Labour administrations since 1997, revealed that although this subject area is awash with literature in the form of government policy, opinion and national evaluations, there is little independent research and systematic review. 4 The current evidence available confirms the presence of continued structural, procedural and cultural barriers that impede effective partnership working in interagency collaborations aimed at crime reduction. Key difficulties include conflicting targets imposed by individual agencies, and divergent ethical and professional values of the different agencies involved across the care control divide.…”
Section: Challengesmentioning
confidence: 73%
“…Även i andra länder i väst, särskilt i Storbritannien, har forum och modeller för samverkan med syfte att minska brottsligheten växt fram. Detta sker utifrån övertygelsen om vinsterna med interprofessionellt samarbete, men också utifrån att krympande resurser och specialisering inom välfärdssektorn kräver fler "händer" och kompetenser för att nå framgång (Danermark & Kullberg 1999, Forkby & Larsen 2005, Williams 2009, Lindberg 2009.…”
Section: Brottspreventiv Samverkanunclassified
“…Detta gäller även för de samverkansformer som växt fram i brottsförebyggande syfte. Här betonas ofta även etiska problem som uppstår när information ska utbytas mellan samverkansaktörerna och man lyfter också fram de överlag ganska stora skillnader mellan professioner som gäller kultur, etik och ibland även hur av partnerskap och samverkan definieras av de olika aktörerna (Williams 2009). …”
Section: Brottspreventiv Samverkanunclassified
See 1 more Smart Citation
“…A possible solution is that clear agreements are set down concerning what information can be exchanged between the two partners when a minor is admitted to a mental health service, as has been mentioned in previous research (Darlington et al, 2005;Lane & Turner, 1999). Certain conditions are required to facilitate this information exchange: establishing clear written protocols (Darlington et al, 2005;Lane & Turner, 1999); organising joint case conferences (Darlington & Feeney, 2008); shared information systems (Chuang & Wells, 2010); and negotiated professional values (Williams, 2009). However, since the different actors saw youth psychiatrists as being in an advisory role to the juvenile judge, more is needed than simply agreements on information exchange.…”
Section: The Role Of the Youth Psychiatristmentioning
confidence: 99%